2022
DOI: 10.3390/ijms232012483
|View full text |Cite
|
Sign up to set email alerts
|

Importance of FaWRKY71 in Strawberry (Fragaria × ananassa) Fruit Ripening

Abstract: WRKY transcription factors play a nonnegligible role in plant growth and development, but little is known about the involvement of WRKY transcription factors in the regulation of fruit ripening. In this study, FaWRKY71 was identified to be closely related to fruit maturation in octoploid strawberry. FaWRKY71 protein localized in the nucleus and responded to cold, salt, low phosphate, ABA, and light quality in strawberry seedlings. The temporal and spatial pattern expression analysis indicated that FaWRKY71 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 58 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…Red strawberry ( Fragaria × ananassa ) ‘Benihoppe’ and its natural white-fleshed mutant ‘Xiaobai’ were grown in a greenhouse at Sichuan agricultural university, China. Six fruit ripening stages defined as small green (SG), big green (BG), white (W), initial red (IN), partial red (PR), and full red (R) were harvested in December ( Yue et al., 2022 ). The skin (outer red layer including achenes) and flesh (inner layer) were manually separated, then frozen in liquid nitrogen immediately.…”
Section: Methodsmentioning
confidence: 99%
“…Red strawberry ( Fragaria × ananassa ) ‘Benihoppe’ and its natural white-fleshed mutant ‘Xiaobai’ were grown in a greenhouse at Sichuan agricultural university, China. Six fruit ripening stages defined as small green (SG), big green (BG), white (W), initial red (IN), partial red (PR), and full red (R) were harvested in December ( Yue et al., 2022 ). The skin (outer red layer including achenes) and flesh (inner layer) were manually separated, then frozen in liquid nitrogen immediately.…”
Section: Methodsmentioning
confidence: 99%
“…The research found that WRKY TFs also involve in fruit development (Chen et al 2019). Lei et al (2020) reported that FvWRKY71 regulates strawberry owering, while Yue et al (2022) discovered that FaWRKY71 promotes strawberry fruit ripening through auxin in strawberries. Our study revealed that 10 FaWRKY71 were highly expressed, especially FxaYL_641g0155700 having the highest expression in the red fruit stage.…”
Section: Discussionmentioning
confidence: 99%
“…PbWRKY75 has shown to promote anthocyanin synthesis in pear by binding the promoters of dihydroflavonol 4-reductase ( PbDFR ) and PbUFGT ( Cong et al., 2021 ). FaWRKY71 stimulates anthocyanin accumulation in strawberry ( Fragaria×ananassa ) by upregulating genes in the synthetic pathway [ flavonoid 3’-hydroxylase ( FaF3’H ), FaLAR , FaANR , anthocyanin transporter genes transparent testa 19 ( FaTT19 ) and transparent testa 12 ( FaTT12 )] ( Yue et al., 2022 ).…”
Section: Mechanism Of Wrky Affecting Flavonoid Synthesismentioning
confidence: 99%